Electrospun Polycaprolactone (PCL) Nanofibers Induce Elongation and Alignment of Co-Cultured Primary Cortical Astrocytes and Neurons - Kayleigh Nutt; Zoe Dombros-Ryan; Ruxandra Birea; Emily Victoria Franks; Sarah Eastham; Morgan Godwin; Chris F. Adams; Divya Maitreyi Chari; Stuart Iain Jenkins (Micromachines)
Neuromimetic in vitro models, simulating in vivo architecture/organization, are urgently needed to reduce experimental reliance on live animals. Our group recently reported a novel brain tissue derivation protocol, simultaneously deriving all major cortical cell types (including immune cells) in a facile protocol, generating a network of neurons in a single growth medium, which was interfaced with nanomaterials. This represents a significant advance, as tissue engineers overwhelmingly use diverse methods to derive and combine individual brain cells for materials-interfacing. However, this multicellular model lacked cellular directionality/structural organization (unlike the highly organized cortical circuits in vivo). Synthetic nanofiber constructs are of high value in tissue engineering, providing directional cues for cells. Most neuro-nanofiber studies employ simple monocultures of astrocytes/neurons and commonly use peripheral neurons rather than central nervous system populations. Here, we have interfaced our complex brain model (neurons/astrocytes derived simultaneously) with randomly oriented or aligned polycaprolactone (PCL) fiber meshes. Both cell types showed targeted extension along aligned fibers versus coverslips or random fibers. A new analysis method developed in-house demonstrated that peak orientations for astrocytes and neurons correlated with aligned nanofibers. Our data support the concept that nanofiber scaffolds can achieve organized growth of mixed cortical neural cell populations, mimicking neural architecture.